CNS tumor with EP300: :BCOR fusion: discussing its prevalence in adult population - Tauziède-Espariat, Arnault; Uro-Coste, Emmanuelle; Sievers, Philipp; Nicaise, Yvan; Mariet, Cassandra; Siegfried, Aurore; Pierron, Gaëlle; Guillemot, Delphine; Benzakoun, Joseph; Pallud, Johan; Roques, Margaux; Bonneville, Fabrice; et al. (Acta Neuropathologica Communications, 2023)
The Central Nervous System (CNS) tumor with BCOR internal tandem duplication (ITD) has recently been added as a novel embryonal histomolecular tumor type to the 2021 World Health Organization (WHO) Classification of CNS Tumors. In addition, other CNS tumors harboring a BCOR/BCORL1 fusion, which are defined by a distinct DNA-methylation profile, have been recently identified in the literature but clinical, radiological and histopathological data remain scarce. Herein, we present two adult cases of CNS tumors with EP300::BCOR fusion. These two cases presented radiological, histopathological, and immunohistochemical homologies with CNS tumors having BCOR ITD in children. To compare these tumors with different BCOR alterations, we performed a literature review with a meta-analysis. CNS tumors with EP300::BCOR fusion seem to be distinct from their BCOR ITD counterparts in terms of age, location, progression-free survival, tumor growth pattern, and immunopositivity for the BCOR protein. CNS tumors from the EP300::BCOR fusion methylation class in adults may be added to the future WHO classification.
Gesehen am 05.04.2023